Penguatan Profil Pelajar Pancasila Dimensi Ketakwaan melalui Kegiatan Keagamaan di Sekolah - Oktafirdayanti Afifatimah; Achmad Muthali'in (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to determine the reinforcement, constraints, and solutions to overcome obstacles to strengthening the profile of Pancasila students in the dimension of piety through religious activities. This study uses a qualitative research method with a case study design. The object of this research is the profile of Pancasila students in the dimension of taqwa and religious activities at Public Junior High School of Sawit 2. The research subjects were school principals, religious teachers (Islam and Christianity), and seventh-grade students. Observations, interviews, and documentation to collect data. The analysis technique used in this study is the flow analysis model technique. The research results show that strengthening Pancasila student profiles in the dimension of taqwa through religious activities has been carried out routinely and effectively. Religious activities for Muslim students consist of morning prayers before starting activities, reading the Qur'an, reading asmaul husna, congregational midday prayers, congregational friday prayers, friday taqwa, infaq students, and ‘Asr prayers before going home. Meanwhile, religious activities for Christian students include morning prayer before starting activities, singing, praising God, reading the Bible, infaq students, and reading and listening to words. There are still some obstacles in its implementation, but they can be overcome by implementing several solutions. In conclusion, religious activities can strengthen the Pancasila student profile and increase student piety.